Investigation of greenhouse gas emissions from municipal solid waste management practices using an economic input-output life cycle analysis approach - ORAK, NUR HANİFE (My University, 2023)
The urban solid waste management is gaining attention due to ecological, economic, and demographic factors, emphasizing the importance of sustainable practices and infrastructure development. There are two main objectives of this work: developing an effective framework to predict the environmental impacts of alternative packaging waste collection rates and estimating the associated environmental emissions, energy consumption, and the materials required for goods and services for the case of Avcilar Municipality in Istanbul City, Türkiye. To achieve these objectives, an Economic Input-Output Life Cycle Assessment model was implemented to assess the impacts of all associated industrial sectors. The results showed that as the amount of packaging waste collection increases, the top two sectors that are responsible for the most emissions are Oil and Gasoline Production and Electricity Production and Supply sectors. In addition, the economic analysis results of the study show that as the packaging waste collection rate increases, the unit packaging waste collection cost decreases. The findings of this study provide valuable insights into the environmental emissions of packaging waste management strategies. Moreover, this study highlights the importance of packaging waste management in reducing overall greenhouse gas emissions and promoting more sustainable waste management practices. Policymakers and waste management stakeholders can utilize this framework to identify strategies that minimize environmental impacts and carbon footprints, thereby fostering a transition towards more sustainable waste management options.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Social Sciences and Humanities; Management; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Mühendislik; Ekonomi ve İş; ENERJİ VE YAKITLAR; İŞLETME; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENGINEERING; ECONOMICS & BUSINESS; ENERGY & FUELS; BUSINESS; ENGINEERING, MANUFACTURING; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Genel Mühendislik; Strateji ve Yönetim; Sosyal Bilimler ve Beşeri Bilimler; Endüstri ve İmalat Mühendisliği; Renewable Energy, Sustainability and the Environment; Physical Sciences; General Engineering; Strategy and Management; Social Sciences & Humanities; Industrial and Manufacturing Engineering; GHGs; IO-LCA; Packaging waste; Solid waste management